2009
DOI: 10.1111/j.1365-2249.2009.03950.x
|View full text |Cite
|
Sign up to set email alerts
|

The rise and rise ofStaphylococcus aureus: laughing in the face of granulocytes

Abstract: SummaryRecent developments in the study of host-pathogen interactions have fundamentally altered our understanding of the nature of Staphylococcus aureus infection, and previously held tenets regarding the role of the granulocyte are being cast aside. Novel mechanisms of pathogenesis are becoming evident, revealing the extent to which S. aureus can evade neutrophil responses successfully by resisting microbicides, surviving intracellularly and subverting cell death pathways. Developing a detailed understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 112 publications
1
49
0
2
Order By: Relevance
“…This was unexpected, since we predicted that neutrophil challenge would enhance bacterial virulence factor expression to interfere with recognition/killing mechanisms. While recent studies have demonstrated the ability of S. aureus to survive intracellularly within neutrophils and, to a lesser extent, macrophages, one would expect this adaptation to necessitate large-scale transcriptional changes (39). One possibility to explain the discrepancy between macrophages and neutrophils in regulating biofilm transcriptional responses is that neutrophils were added to biofilms at a 10-fold-lower density than macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected, since we predicted that neutrophil challenge would enhance bacterial virulence factor expression to interfere with recognition/killing mechanisms. While recent studies have demonstrated the ability of S. aureus to survive intracellularly within neutrophils and, to a lesser extent, macrophages, one would expect this adaptation to necessitate large-scale transcriptional changes (39). One possibility to explain the discrepancy between macrophages and neutrophils in regulating biofilm transcriptional responses is that neutrophils were added to biofilms at a 10-fold-lower density than macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…S taphylococcus aureus can act as a peaceful colonizer of the skin and the nostrils or as an aggressive pathogen causing invasive diseases and sepsis. Intracellular survival of S. aureus, abscess formation, as well as the emergence of methicillin-resistant strains complicate the treatment of serious infections (1). S. aureus also produces virulence factors such as hemolytic and leucolytic toxins and C-targeting factors that contribute to immune evasion (2).…”
mentioning
confidence: 99%
“…Additionally, quorum sensing molecules control neutrophil ROS response and penetration into P. aeruginosa bioilms [60]. Similarly, Aggregatibacter actinomycetemcomitans and S. aureus produce bacterial toxins that induce neutrophils lysis and degranulation [61][62][63]. In addition to directly atacking neutrophils, dysbiotic microbiota in bioilms can render themselves resistant to neutrophil-mediated killing by disguising their immunogenicity.…”
Section: Dysbiotic Bacteriamentioning
confidence: 99%
“…For example, P. aeruginosa bioilms produce bacterial surfactants that induce rapid neutrophil death [59], and Aggregatibacter actinomycetemcomitans and S. aureus produce bacterial toxins that induce neutrophil lysis and degranulation [61][62][63]. These bacterial products could be neutralized with antibodies or novel pharmaceutical drugs to prevent their negative efects on neutrophils.…”
Section: Therapeutic Approachesmentioning
confidence: 99%